Automatic Analysis of Applications for Portability Across Linux Distributions - Rubanov, Vladimir (Electronic Communications of the EASST, 2009)
Problems with portability of applications across various Linux distributions is one of the major sore spots of independent software vendors (ISVs) wishing to support the Linux platform in their products. The source of the problem is that different distributions have different sets of system libraries that vary in the interfaces (APIs) provided, with respect to both composition and behavior. And the critical questions arise such as "which distributions my application would run on" or "what can I specifically do to make my application run on a greater number of distributions". This article presents an approach and the Linux Application Checker tool that help to answer such questions by automatically analyzing the target application and confronting collected data with the internal knowledge base containing information about the various real world distributions. Additionally, Linux Application Checker is an official tool approved by the Linux Foundation for certifying applications for compliance with the Linux Standard Base (LSB) standard, the leading effort for the "single Linux specification".